2005
DOI: 10.1139/w04-127
|View full text |Cite
|
Sign up to set email alerts
|

Tricalcium phosphate solubilizing abilities ofTrichodermaspp. in relation to P uptake and growth and yield parameters of chickpea (Cicer arietinumL.)

Abstract: Nine isolates of Trichoderma spp. were investigated for their ability to solubilize insoluble phosphate in Pikovskaya's broth and were compared with an efficient phosphate-solubilizing bacterium Bacillus megaterium subsp. phospaticum PB that was used as the reference strain. All 9 Trichoderma isolates were found to solubilize insoluble tricalcium phosphate to various extents. Trichoderma viride (TV 97) (9.03 microg x mL(-1)), Trichoderma virens (PDBCTVs 12) (9.0 microg x mL(-1)), and Trichoderma virens (PDBCTV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(42 citation statements)
references
References 16 publications
0
37
0
5
Order By: Relevance
“…The absence of response after BE application was observed in many other experiments [45,48,49] and in particular in soils characterized by extraordinary low levels of available P (20 mg kg −1 or lower) or that were limiting in other soil nutrients [10,50,51]. In contrast, other studies have shown that for maize and other crops, the application of BEs was more efficient in the absence of added P fertilizers [36][37][38]. However, in these cases, soil P availability was distinctly higher and P CAL ranged between 35 and 45 mg/kg.…”
Section: Moderate Effects In the Absence Of Added P (P0 Be1-3)mentioning
confidence: 88%
See 1 more Smart Citation
“…The absence of response after BE application was observed in many other experiments [45,48,49] and in particular in soils characterized by extraordinary low levels of available P (20 mg kg −1 or lower) or that were limiting in other soil nutrients [10,50,51]. In contrast, other studies have shown that for maize and other crops, the application of BEs was more efficient in the absence of added P fertilizers [36][37][38]. However, in these cases, soil P availability was distinctly higher and P CAL ranged between 35 and 45 mg/kg.…”
Section: Moderate Effects In the Absence Of Added P (P0 Be1-3)mentioning
confidence: 88%
“…The choice of these three BEs is based on their published ability to act as potential bio-stimulants and biofertilizers. The strain Trichoderma harzianum Rifai 1295-22 (T22) has demonstrated abilities to increase the solubilization of sparingly soluble calcium phosphates [34] and to promote plant growth in various plant species [35,36] including maize [37]. The strain Pseudomonas DSMZ 13134 is an efficient root colonizer [38] and has been shown to solubilize inorganic phosphate under in vitro conditions [39].…”
Section: Be Treatmentsmentioning
confidence: 99%
“…The concept of BEs covers quite a diverse group of natural products [15]. In the present paper, the scope was limited to plant growth-promoting microorganisms (PGPM) focusing on plant growth-promoting rhizobacteria (PGPR) [16] and free-living fungi, such as species of the genus Trichoderma [17]. PGPM may have the potential to enhance plant uptake of P from soil [14,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…PGPM may have the potential to enhance plant uptake of P from soil [14,18,19]. Improved growth under P-limiting soil conditions as a result of microbial inoculations has been observed in many different plant species, such as mung bean [17], bean [20], maize [21] and wheat [22]. In soil, a large proportion of the total P pool is not directly available for plant uptake [23], and the ability to solubilise phosphates in the rhizosphere has been viewed as an important function of PGPM [24].…”
Section: Introductionmentioning
confidence: 99%
“…Trichoderma sp. is a free-living fungi commonly found in soil and root system and it is known to dissolve phosphate and micro nutrients (Rudresh et al, 2005;Saravanakumar et al, 2013). Interaction Trichoderma sp.…”
Section: Introductionmentioning
confidence: 99%